Bounds on Malapportionment - László Á. Kóczy; Balázs Sziklai (Hungarian Academy of Sciences, Institute of Economics, 2018)
Uniformly sized constituencies give voters similar influence on election outcomes. When constituencies are set up, seats are allocated to the administrative units, such as states or counties, using apportionment methods. According to the impossibility result of Balinski and Young, none of the methods satisfying basic monotonicity properties assign a rounded proportional number of seats (the Hare-quota). We study the malapportionment of constituencies and provide a simple bound as a function of the house size for an important class of divisor methods, a popular, monotonic family of techniques.
Keywords: D72; D78; 330; apportionment problem; divisor methods; malapportionment; Harequota